Positive pole piece, secondary battery and electric device

By setting the first and second regions with different particle size distribution indexes in the positive electrode sheet, the problem of improving energy density and safety of the secondary battery is solved, and the synchronous optimization of high compaction density and flexibility is achieved.

CN119324204APending Publication Date: 2025-01-17CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 5 Cited by

Patent Information

Application Number
CN202310875559.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

While increasing the energy density of secondary batteries, maintaining battery safety has become a challenge, and the prior art can easily lead to brittle fracture of the pole and safety problems.

Method used

A positive electrode sheet is designed, by providing a first region and a second region in the positive electrode film layer, in which the particle size distribution index of the active material is smaller than the second region, so as to achieve uniform distribution and size classification of the active material. Improve the flexibility and compaction density of the pole sheet to reduce the risk of brittle breakage.

Benefits of technology

It achieves the improvement of battery energy density while maintaining good flexibility and safety performance, reduces the possibility of brittle breakage of the pole sheet, and improves the overall safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324204A_ABST
    Figure CN119324204A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece, a secondary battery and an electric device. The positive pole piece comprises a current collector and a positive pole film layer located on at least one side of the current collector, the positive pole film layer comprises a first region and a second region, and the particle size distribution index of an active material in the first region is smaller than that of an active material in the second region; the particle size distribution index refers to the ratio of the standard deviation of the particle size of the active material to the average particle size, and the first region refers to a region where the vertical extension distance of the positive electrode film layer from the surface of one side close to the current collector to the direction of the positive electrode film layer is within h1; the second region is a region where the positive electrode film layer vertically extends from the surface of one side close to the current collector to the positive electrode film layer by a distance of h1 to H, H is the thickness of the positive electrode film layer, and h1 is smaller than H.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] In recent years, as secondary batteries have been widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's performance requirements for secondary batteries have become increasingly higher.

[0003] Improving the energy density of secondary batteries has become the main pursuit of the market. However, the increase in the energy density of secondary batteries often easily leads to battery safety issues. How to improve the energy density of batteries while maintaining battery safety has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the problems existing in the background technology, the present application provides a positive electrode plate, which aims to increase the volume energy density of the battery while improving the flexibility of the plate, reducing the possibility of brittle fracture of the plate, and simultaneously improving the safety performance of the battery.

[0005] A first aspect of the present application provides a positive electrode plate, comprising a current collector and a positive electrode film layer located on at least one side of the current collector, the positive electrode film layer comprising a first region and a second region, the particle size distribution index of the active material in the first region is smaller than the particle size distribution index of the active material in the second region, wherein the particle size distribution index refers to the ratio of the standard deviation of the active material particle size to the average particle size, the first region refers to a region where the positive electrode film layer extends from a surface close to one side of the current collector toward the positive electrode film layer within a distance of h1, and the second region refers to a region where the positive electrode film layer extends vertically from a surface close to one side of the current collector toward the positive electrode film layer for a distance of h1 to H, wherein H is the thickness of the positive electrode film layer, and h1 is less than H. Optionally, the difference between the particle size distribution index of the active material in the second region and the particle size distribution index of the active material in the first region is 0.08-0.80, and can be optionally 0.20-0.70.

[0006] The uniform distribution of active materials in the first region can achieve good slippage between active materials, significantly improving the flexibility of the positive electrode sheet after cold pressing. At the same time, the size grading of active materials in the second region is beneficial to improving the compaction density of the positive electrode sheet, so that the positive electrode sheet can maintain good flexibility while achieving a high compaction density, so as to maintain the safety performance of the battery while improving the battery energy density.

[0007] In any embodiment, the particle size distribution index of the active material in the first region is 0.05 to 0.52, and can be optionally 0.1 to 0.5.

[0008] The particle size distribution index of the active material in the first region is 0.05-0.52, indicating that the particle size of the active material in the first region is uniform, so that the pole piece has good flexibility while having a high compaction density. The particle size distribution index of the active material in the first region is 0.1-0.5, the flexibility of the pole piece is further improved, the cost is further reduced, and the pole piece is not easy to break or crack during processing and circulation, so that the safety of the battery is further guaranteed.

[0009] In any embodiment, the particle size distribution index of the active material in the second region is 0.60 to 0.82, and can be optionally 0.65 to 0.78.

[0010] The particle size distribution index of the active material in the second region is 0.60-0.82, indicating that the particle size dispersion of the active material in the second region is large and has a size gradation relationship, which is conducive to achieving tight filling to increase the compaction density and improve the volume energy density of the battery.

[0011] In any embodiment, the average particle size of the active material in the first region is 150 nm to 2000 nm, and optionally 300 nm to 2000 nm.

[0012] The particle size of the active material in the first region is moderate, with fewer large single crystal particles at the micron level, resulting in less damage to the substrate. This allows for both the battery capacity and the flexibility of the electrode, achieving simultaneous optimization of the battery's volume energy density and safety performance.

[0013] In any embodiment, in the second region, based on the total amount of active materials, the percentage of active materials having a particle size of 50 nm-200 nm is 10%-50%, and optionally 10%-25%.

[0014] The presence of small-particle active materials helps to achieve close packing of the second region, thereby improving the compaction density and energy density. In addition, the small particle size can reduce the diffusion distance of active ions and improve the power performance and low-temperature performance of the battery.

[0015] In any embodiment, in the second region, based on the total cross-sectional area of ​​the active material, the cross-sectional area percentage of the active material having a particle size of not less than 1500 nm is 5%-25%, optionally 10%-25%.

[0016] The above arrangement enables the active material in the second region to produce size grading and achieve close stacking, which is beneficial to the improvement of the battery's ultimate compaction density and volume energy density.

[0017] In any embodiment, the specific surface area of ​​the active material in the first region is 4-14 m 2 / g, optional 6-12m 2 / g.

[0018] There are fewer active materials with extremely small particle sizes in the first region, and the specific surface area of ​​the active materials is lower, which helps to reduce the amount of binder used, thereby increasing the active material loading, increasing the volume energy density of the battery, while improving the flexibility of the pole piece and enhancing the safety performance of the battery.

[0019] In any embodiment, the mass percentage of the binder in the first region is lower than the mass percentage of the binder in the second region, the mass percentage of the binder in the first region is the ratio of the mass of the binder in the first region to the mass of the positive electrode film layer in the first region, and the mass percentage of the binder in the second region is the ratio of the mass of the binder in the second region to the mass of the positive electrode film layer in the second region.

[0020] The binder in the positive electrode active material layer is mostly crystalline or semi-crystalline material with a high elastic modulus. The high binder content makes it difficult for the positive electrode film to displace or deform under external force. Therefore, when the pole piece is bent, the binder is prone to intercrystalline cracks, causing the positive electrode film to fracture. Reducing the mass percentage of the binder in the first region is conducive to further improving the flexibility of the pole piece.

[0021] In any embodiment, the mass percentage of the binder in the first region is 0.5%-2.5%, and optionally 1.5%-2%.

[0022] In any implementation manner, the ratio of h1 to H satisfies 1:10 to 5:10, and may be 2:10-4:10.

[0023] When the thickness ratio of the first region to the positive electrode film layer is within the above range, the energy density and safety of the battery can be improved simultaneously.

[0024] In any embodiment, the surface density of the positive electrode film layer is 350 mg / 1540.25 cm 2 -500mg / 1540.25cm 2 .

[0025] The positive electrode plate provided in the present application is particularly suitable for thick electrode plate design.

[0026] In any embodiment, the active material in the first region and / or the second region comprises a polyanionic compound.

[0027] The positive electrode plate provided in the present application can effectively solve the problem of low compaction density of polyanion compounds while ensuring the flexibility of the plate, thereby effectively improving the volume energy density of the battery.

[0028] In any embodiment, the positive electrode film layer is prepared by one-time coating using a double-sided double-cavity coater.

[0029] The one-time coating preparation of the double-sided double-cavity coater helps to improve efficiency and increase production capacity.

[0030] A second aspect of the present application provides a secondary battery, comprising the positive electrode plate of the first aspect.

[0031] The secondary battery provided in the present application has both excellent volume energy density and safety performance.

[0032] A third aspect of the present application provides an electrical device, comprising the secondary battery of the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;

[0034] Figure 2 is a scanning electron microscope image of the positive electrode film layer of Example 1 of the present application;

[0035] Figure 3 It is a particle size map obtained by processing the scanning electron microscope image of the cross section of the electrode piece using the Avizo 3D software of one embodiment of the present application; (A) is the particle size map of the second area, and (B) is the particle size map of the first area.

[0036] Figure 4 yes Figure 2 SEM image of the first region in the middle;

[0037] Figure 5 yes Figure 2 SEM image of the second area in the middle;

[0038] Figure 6 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0039] Figure 7 yes Figure 6 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0040] Figure 8 It is a schematic diagram of an electrical device according to one embodiment of the present application.

[0041] Reference numerals:

[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 positive electrode plate; 61 current collector; 62 positive electrode film layer; 621 first region; 622 second region. DETAILED DESCRIPTION

[0043] Below, the embodiments of the positive electrode plate, secondary battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0048] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0049] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0050] Improving the compaction density of the pole piece is one of the effective means to improve the energy density of the battery. However, the increase in compaction density will make the pole piece brittle, which is easy to cause the pole piece to break during the processing or recycling process of the pole piece. The broken pole piece is easy to puncture the diaphragm, causing the positive pole piece to directly contact the negative pole piece, thus forming a short circuit and causing battery safety problems.

[0051] [Positive electrode]

[0052] Based on this, Figure 1As shown, the present application provides a positive electrode plate 6, including a current collector 61 and a positive electrode film layer 62 located on at least one side of the current collector, the positive electrode film layer 62 includes a first region 621 and a second region 622, the particle size distribution index of the active material in the first region 621 is smaller than the particle size distribution index of the active material in the second region 622, wherein the particle size distribution index refers to the ratio of the standard deviation of the particle size of the active material to the average particle size, the first region 621 refers to the region where the positive electrode film layer 62 extends vertically from the surface close to the current collector 61 to the positive electrode film layer 62 within a distance of h1, the second region 622 refers to the region where the positive electrode film layer 62 extends vertically from the surface close to the current collector 61 to the positive electrode film layer 62 for a distance of h1 to H, wherein H is the thickness of the positive electrode film layer 62, h1 is less than H, and optionally, the difference between the particle size distribution index of the active material in the second region and the particle size distribution index of the active material in the first region is 0.08-0.80, and can be optionally 0.20-0.70.

[0053] The structure of the positive electrode plate 6 can be characterized by any known method in the art. As an example, an argon ion beam is used to cut the plate perpendicular to the large surface of the plate to expose the cross section, and the cross section is photographed by a scanning electron microscope, and the particle size of the active material in each layer is statistically analyzed. The scanning electron microscope image is shown in FIG. Figure 2 shown.

[0054] The particle size of the positive electrode active material can be characterized by any method known in the art. As an example, the particle size of the positive electrode active material is calculated by the area equivalent circle diameter statistical method. Figure 3 As shown, the cross-sectional scanning electron microscope image of the positive electrode piece is used to distinguish particles and count the area of ​​a single particle using Avizo 3D software, and the equivalent circle diameter is calculated based on the area of ​​each particle counted by the software, thereby obtaining the particle size value of each particle.

[0055] The particle size distribution index PDI has a well-known meaning in the art and can be measured by a test method and a test instrument well-known in the art. The particle size distribution index PDI is an important parameter for measuring the uniformity of particle size. The lower the particle size distribution index PDI, the smaller the particle size deviation value, and the higher the uniformity of particle size.

[0056] The particle size distribution index (PDI) is the standard deviation of the particle size divided by the average particle size.

[0057]

[0058]

[0059] Where σ is the standard deviation of particle size, x i is the particle size value, is the average particle size, n is the total number of particles counted, and the average particle size is the total particle size value divided by the total number of particles counted.

[0060] As an example, the positive electrode current collector 61 has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer 62 is disposed on any one or both of the two opposite surfaces of the positive electrode current collector 61 .

[0061] In some embodiments, the positive electrode current collector 61 may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0062] In some embodiments, the thickness of the positive electrode current collector 61 is 10 um-20 um.

[0063] A positive electrode current collector 61 of a certain thickness can reduce the possibility of breakage of the positive electrode sheet and improve the safety performance of the battery.

[0064] Depend on Figure 3-Figure 5 It can be seen that the particle size distribution index of the active material in the first region 621 is smaller than that of the active material in the second region 622, indicating that the particle size distribution of the active material in the first region 621 is more uniform than that of the active material in the second region 622. The uniform distribution of the active material in the first region 621 can achieve good slippage between the active materials, significantly improving the flexibility of the positive electrode sheet 6 after cold pressing, while the size gradation of the active material in the second region 621 is conducive to improving the compaction density of the positive electrode sheet 6, so that the positive electrode sheet 6 maintains good flexibility while achieving a high compaction density, so as to maintain the safety performance of the battery while improving the battery energy density.

[0065] In some embodiments, the difference between the particle size distribution index of the active material in the second region and the particle size distribution index of the active material in the first region is 0.08, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80 or any value therebetween.

[0066] Controlling the difference in particle size distribution index within the above range can effectively increase the ultimate compaction density of the electrode, improve the flexibility of the electrode, and optimize the battery energy density.

[0067] In some embodiments, the particle size distribution index of the active material in the first region is 0.05 to 0.52, and may be 0.1 to 0.5.

[0068] In some embodiments, the particle size distribution index of the active material in the first region may be 0.52, 0.5, 0.45, 0.4, 0.35, 0.3, 0.25, 0.2, 0.1, 0.05, or any value therebetween.

[0069] The particle size distribution index of the active material in the first region is 0.05-0.52, indicating that the particle size of the active material in the first region is uniform, so that the pole piece has good flexibility while having a high compaction density. When the particle size distribution index of the active material in the first region is 0.1-0.5, the flexibility of the pole piece is further improved, the cost is reduced, and the safety and economy of the battery are further guaranteed.

[0070] In some embodiments, the particle size distribution index of the active material in the second region is 0.60 to 0.82, and optionally 0.65 to 0.78.

[0071] In some embodiments, the particle size distribution index of the active material in the second region may be 0.60, 0.62, 0.64, 0.65, 0.68, 0.70, 0.73, 0.76, 0.78, 0.82, or any value therebetween.

[0072] The particle size distribution index of the active material in the second region is 0.60-0.82, indicating that the particle size dispersion of the active material in the second region is large and has a size gradation relationship, which is conducive to achieving tight filling to increase the compaction density and improve the volume energy density of the battery.

[0073] In some embodiments, the average particle size of the active material in the first region is 150 nm to 2000 nm, and optionally 300 nm to 2000 nm.

[0074] In some embodiments, the average particle size of the active material in the first region may be 150 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, 1500 nm, 1600 nm, 1700 nm, 1800 nm, 1900 nm, 2000 nm, or any value therebetween.

[0075] The particle size of the active material in the first region is moderate, with fewer large single crystal particles at the micron level, resulting in less damage to the substrate. This allows for both the battery capacity and the flexibility of the electrode, achieving simultaneous optimization of the battery's volume energy density and safety performance.

[0076] In some embodiments, in the second region, based on the total amount of active materials, the percentage of active materials having a particle size of 50 nm to 200 nm is 10% to 50%, and optionally 10% to 25%.

[0077] In some embodiments, in the second region, based on the total amount of active materials, the percentage of active materials with a particle size of 50 nm-200 nm may be 10%, 16%, 20%, 25%, 30%, 40%, 50% or any value therebetween.

[0078] The amount of active material with a particle size of 50nm-200nm can be tested by any known method in the art. As an example, it is calculated by dividing the amount of active material with a particle size of 50nm-200nm in the cross-sectional scanning electron microscope image by the total amount of active material counted.

[0079] The presence of small-particle active materials helps to achieve close packing of the second region, thereby improving the compaction density and energy density. In addition, the small particle size can reduce the diffusion distance of active ions and improve the power performance and low-temperature performance of the battery.

[0080] In some embodiments, in the second region, based on the total cross-sectional area of ​​the active material, the cross-sectional area percentage of the active material having a particle size of not less than 1500 nm is 5%-25%, optionally 10%-25%.

[0081] In some embodiments, in the second region, based on the total cross-sectional area of ​​the active material, the cross-sectional area percentage of the active material with a particle size of not less than 1500 nm may be 5%, 10%, 15%, 19%, 20%, 25% or any value therebetween.

[0082] The cross-sectional area percentage of the active material with a particle size of not less than 1500 nm can be tested by any known method in the art. As an example, it is calculated by dividing the cross-sectional area of ​​the active material with a particle size of not less than 1500 nm in the cross-sectional scanning electron microscope image by the total area of ​​the statistical active material. The cross-sectional area of ​​the active material can be obtained by statistically analyzing the scanning electron microscope image of the electrode section using Avizo 3D software.

[0083] The above arrangement enables the active material in the second region to produce size grading and achieve close stacking, which is beneficial to the improvement of the battery's ultimate compaction density and volume energy density.

[0084] In some embodiments, the specific surface area of ​​the active material in the first region is 4-14 m 2 / g, optional 6-12m 2 / g.

[0085] In some embodiments, the specific surface area of ​​the active material in the first region may be 4 m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g or any value therebetween.

[0086] There are fewer active materials with extremely small particle sizes in the first region, and the specific surface area of ​​the active materials is lower, which helps to reduce the amount of binder used, thereby increasing the active material loading, increasing the volume energy density of the battery, while improving the flexibility of the pole piece and enhancing the safety performance of the battery.

[0087] In some embodiments, the mass percentage of the binder in the first region is lower than the mass percentage of the binder in the second region, the mass percentage of the binder in the first region is the ratio of the mass of the binder in the first region to the mass of the positive electrode film layer in the first region, and the mass percentage of the binder in the second region is the ratio of the mass of the binder in the second region to the mass of the positive electrode film layer in the second region.

[0088] In some embodiments, the binder includes a fluoropolymer, and the fluoropolymer includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0089] The binder in the positive electrode film layer is mostly crystalline or semi-crystalline material with a high elastic modulus and is difficult to deform under external force. Therefore, when the positive electrode sheet with a high binder content is bent, the positive electrode film layer is difficult to displace or deform under external force, and the binder is prone to intercrystalline cracks, causing brittle fracture of the active material layer. Reducing the mass percentage of the binder in the first region is conducive to further improving the flexibility of the electrode sheet.

[0090] In some embodiments, the mass percentage of the binder in the first region is 0.5%-2.5%, and optionally 1.5%-2%.

[0091] In some embodiments, the mass percentage of the binder in the first region may be 0.5%, 1%, 1.5%, 2%, 2.5% or any value therebetween.

[0092] In some embodiments, the ratio of h1 to H is 1:10 to 5:10, and can be 2:10-4:10.

[0093] In some embodiments, the ratio of h1 to H can be 1:10, 2:10, 3:10, 4:10, 5:10 or any value therebetween.

[0094] When the ratio of the thickness h1 of the first region to the thickness H of the positive electrode film layer is within the above range, the energy density and safety of the battery can be improved simultaneously.

[0095] In some embodiments, the surface density of the positive electrode film layer is 350 mg / 1540.25 cm 2 -500mg / 1540.25cm 2 .

[0096] The positive electrode provided by the present application is particularly suitable for thick electrode design. The double-layer design of the electrode improves the problems of unstable cavity pressure, large weight fluctuation, and poor electrode uniformity during single-layer electrode coating, thereby effectively improving the quality of the electrode.

[0097] Moreover, thick pole pieces are more prone to cracking than ordinary pole pieces. The cracking phenomenon refers to the compression of the inner film layer during hot pressing and shaping after the battery cell is wound. The positive electrode active material on the inner film layer is squeezed and deformed in the restrained space, which exerts an extrusion force on the current collector and the outer film layer, causing the current collector or the outer film layer to be broken due to insufficient tension resistance, thereby generating cracks or pinholes, causing the pole piece to become light-transmissive. Since the extrusion force of the inner film layer of thick pole pieces is large, cracking is more common in thick pole pieces. The uniform distribution of active materials in the first region can effectively disperse the extrusion force generated by the inner film layer, thereby reducing the probability of cracking.

[0098] In some embodiments, the active material in the first region and / or the second region comprises a polyanionic compound.

[0099] The general formula of polyanionic compounds is as follows

[0100] Ne x M y (A z O k ) m Z w

[0101] Among them, Ne includes at least one of Na and Li, M includes at least one of Fe, Mn, Ni, Co, Ti, V, Cr, V, Ca, Mg, and Al, A includes at least one of Si, S, and P, and Z includes at least one of F and OH, wherein 0.98≤x≤10, 0.94≤y≤10, 0.94≤z≤10, 2≤k≤10, 0.5≤m≤10, and 0<w≤10.

[0102] In some embodiments, the polyanion compound is a complex salt containing an alkali metal whose crystal framework is constructed by a series of tetrahedral and polyhedral anion units, which are mainly divided into olivine structure, NASICON structure, triclinic structure and mixed polyanion compound materials.

[0103] In some embodiments, the polyanionic compound includes lithium iron phosphate, sodium iron phosphate, sodium vanadium phosphate.

[0104] Polyanion compounds have stable structures, good safety performance, high thermal stability, and a wide range of raw materials for processing at low prices. Moreover, during the charge and discharge process, the volume change and structural rearrangement of the material are extremely small, which makes the material have a high operating voltage and excellent stability. However, the electronic conductivity of the bulk phase of polyanion compounds is low, and carbon coating and particle nano-sizing are generally required to improve the electrical conductivity and ionic conductivity. However, carbon-coated and nano-sized polyanion compounds are difficult to process and difficult to compact tightly, making it difficult to effectively increase the compaction density of the pole piece and the volume energy density of the battery.

[0105] The positive electrode plate provided in the present application can effectively solve the problem of low compaction density of polyanion compounds while ensuring the flexibility of the plate, thereby effectively improving the volume energy density of the battery.

[0106] In some embodiments, the positive electrode film layer is prepared by one-time coating using a double-sided double-cavity coater.

[0107] The one-time coating preparation of the double-sided double-cavity coater helps to improve efficiency and increase production capacity.

[0108] In some embodiments, the positive electrode film layer is prepared by multiple coating processes.

[0109] [Negative electrode]

[0110] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0111] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0112] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0113] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0114] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0115] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0116] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0117] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0118] [Electrolytes]

[0119] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0120] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0121] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0122] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0123] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0124] [Isolation film]

[0125] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0126] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0127] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0128] A second aspect of the present application provides a secondary battery, comprising a negative electrode sheet according to any embodiment, and / or a negative electrode sheet prepared by a preparation method according to any embodiment.

[0129] In some embodiments, the secondary battery includes an electrolyte, and the silicon interface layer is located between the electrolyte and the metal layer.

[0130] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0131] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0132] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 6 The secondary battery 5 is a square structure as an example.

[0133] In some embodiments, reference Figure 7 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0134] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0135] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0136] Figure 8The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0137] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0138] Example

[0139] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0140] 1. Preparation method

[0141] Example 1

[0142] 1) Preparation of the first positive electrode slurry

[0143] 96.5wt% of the first positive electrode active material lithium iron phosphate (Dv50 is 800nm, Dv10 is 150nm, Dv90 is 1800nm), 1.0wt% of the conductive agent (conductive carbon black), 2.0wt% of the binder (polyvinylidene fluoride) and 0.5wt% of the dispersant polyvinyl pyrrolidone are mixed, and then N-methylpyrrolidone is added and stirred to disperse and adjust the slurry viscosity to 8000-12000mPa.s to prepare the first positive electrode slurry. Among them, Dv50 is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 50%; Dv10 is the particle size corresponding to the cumulative volume particle size distribution percentage of the sample reaching 10%; Dv90 is the particle size corresponding to the cumulative volume particle size distribution percentage of the sample reaching 50%.

[0144] 2) Preparation of the second positive electrode slurry

[0145] 96.5wt% of the second positive electrode active material lithium iron phosphate (Dv50 is 1200nm, Dv10 is 200nm, Dv90 is 3500nm), 1.0wt% of the conductive agent (conductive carbon black), 2.0wt% of the binder (polyvinylidene fluoride), and 0.5wt% of the dispersant polyvinyl pyrrolidone are mixed, and then N-methylpyrrolidone is added to stir and disperse, and the slurry viscosity is adjusted to 8000-12000mPa.s to prepare a second positive electrode slurry.

[0146] 3) Preparation of positive electrode

[0147] The first positive electrode slurry and the second positive electrode slurry were coated with a double-sided double-cavity coating device at 100 mg / 1540.25 cm 2 、300mg / 1540.25cm 2 The coating weight (referring to the weight of dry material in the slurry) is coated on the aluminum foil at one time, wherein the first positive electrode slurry is coated on the lower layer close to the aluminum foil, which is the first active material layer, located in the first area of ​​the electrode sheet; the second positive electrode slurry is coated on the upper layer, which is the second active material layer, located in the second area of ​​the electrode sheet; after the double-sided coating is completed, the positive electrode sheet is prepared by drying, cold pressing, slitting, and the thickness of the aluminum foil is 15um.

[0148] 4) Preparation of negative electrode sheet

[0149] 95wt% of negative electrode active material (artificial graphite), 1.0wt% of conductive agent (conductive carbon black), 2.0wt% of binder (styrene-butadiene rubber (SBR)) and 2.0wt% of thickener (sodium carboxymethyl cellulose (CMC)) were mixed, deionized water was added and stirred, and the negative electrode slurry was dispersed to form a negative electrode slurry.

[0150] Then the negative electrode slurry is coated on the Cu foil. After both sides are completed, it is dried, cold pressed, cut and sliced ​​to prepare the negative electrode sheet.

[0151] 5) Preparation of batteries

[0152] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with the prepared electrolyte, and packaged, injected, formed, and vented to obtain a lithium-ion battery.

[0153] The preparation methods of Examples 2-21 are similar to those of Example 1, but the particle size of each layer of material, the binder content or the coating quality are changed to adjust the relevant parameters. The specific parameters are shown in Table 1.

[0154] The preparation method of Example 14 is basically the same as that of Example 1, except that the mass content of the positive electrode active material is 97wt%, the mass content of the binder is 1.5%, and the proportion of the small-particle positive electrode active material is reduced to reduce the specific surface area of ​​the positive electrode active material;

[0155] The preparation method of Example 15 is basically the same as that of Example 1, except that the mass content of the positive electrode active material is 96.7wt%, the mass content of the binder is 1.8%, and the proportion of small-particle positive electrode active material is reduced to reduce the specific surface area of ​​the positive electrode active material.

[0156] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that the components of the first active material layer and the second active material layer in Comparative Example 1 are the same as the components of the first active material layer.

[0157] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that the components of the first active material layer and the second active material layer in Comparative Example 2 are the same as the components of the second active material layer.

[0158] The preparation method of Comparative Example 3 is substantially the same as that of Example 1, except that the components of the first active material layer and the second active material layer in Comparative Example 3 are the same as those of the second active material layer and the first active material layer in Example 1, respectively.

[0159] 2. Test Method

[0160] 1) Average particle size and particle size distribution test method

[0161] The electrode piece is cut open perpendicularly to the electrode piece surface by using an argon ion beam to expose the cross section, which is photographed by a scanning electron microscope. The particle size of the active material is statistically analyzed by the length diameter statistical method, such as Figure 3 shown.

[0162] Among them, the average particle size is the total particle size value divided by the total number of particles;

[0163] The particle size distribution index PDI is the standard deviation of the particle size divided by the average particle size.

[0164]

[0165]

[0166] Where σ is the standard deviation of particle size, x i is the particle size value, is the average particle size, and n is the total number of particles counted.

[0167] Since particles with a size of 0<r≤50nm are prone to adhesion, there are large errors in statistics and it is difficult to clearly identify them individually. Therefore, during the particle size statistics process, particles with a size of 0<r≤50nm are not included in the statistical range.

[0168] The amount content of the active material with a particle size of 50nm-200nm is calculated by dividing the amount of the active material with a particle size of 50nm-200nm in the section by the amount of the total active material.

[0169] The cross-sectional area percentage of the active material having a particle size of not less than 1500 nm is calculated by dividing the cross-sectional area of ​​the active material having a particle size of not less than 1500 nm in the end surface by the cross-sectional area of ​​the total active material.

[0170] The cross-sectional area of ​​the active material was obtained by statistically analyzing the scanning electron microscopy images of the electrode sections obtained using Avizo 3D software.

[0171] 2) Specific surface area test method

[0172] The specific surface area was tested by gas adsorption method according to the GB / T19587-2017 test standard, as follows: the positive electrode active material was taken as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures was measured at a relative pressure of 0.05-0.30. The monolayer adsorption amount of the sample was obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of ​​the material.

[0173] 3) Ultimate compaction density test method

[0174] The double-sided coated electrode is cold pressed by a roller press to test the elongation of the electrode after cold pressing and to evaluate the flexibility of the electrode after cold pressing.

[0175] By increasing the pressure of the roller press, pole pieces with different compaction densities will be obtained. As the pressure increases, the compaction density of the pole piece increases, the elongation of the pole piece increases, and the flexibility of the pole piece decreases. Too high an elongation of the pole piece can easily cause the pole piece to warp, and too low a flexibility of the pole piece can easily cause the pole piece to break brittlely. Therefore, the smaller of the compaction density corresponding to the elongation of the pole piece of 6‰ or the number of times the pole piece's flexibility is folded 3 times is defined as the limit compaction density.

[0176] The compacted density is calculated by dividing the mass of the single-sided positive electrode film layer by the volume of the positive electrode film layer.

[0177] The test method for elongation is as follows:

[0178] Lay the electrode flat on a horizontal table and cut it into sections, with each electrode about 100 cm long; remove the copper foil of the electrode edge substrate, and pay attention to keep the cut edge of the electrode parallel to the MD direction of the electrode (perpendicular to the direction of the cold pressing roller), ensure that the electrode part is completely covered by the coating, use a steel ruler to measure the length between the marking points at the same position of the length and width of the head and tail of the electrode, estimate to 0.1mm, and record the length before cold pressing; record the length between the corresponding marking points after cold pressing, and use (length after cold pressing - length before cold pressing) / length before cold pressing as the elongation rate of the electrode.

[0179] The test method for the number of flexible folds is shown below.

[0180] 4) Compacted density is 2.5g / cm 3 The number of times the pole piece can be folded

[0181] The compacted density is 2.5 g / cm3 The positive electrode sheet is cut into 20×100mm 2 Fold the specimen in the forward direction, flatten it with a 2kg roller, unfold it and check against the light to see if there is light transmittance between the gaps. If not, fold it in the reverse direction, flatten it with a 2kg roller, and check against the light again. Repeat this process until light transmittance between the gaps. Record the number of folds. Repeat the test three times and take the average value as the reference data for the flexibility of the electrode.

[0182] 5) Battery volume energy density test method

[0183] The battery at the ultimate compaction density was left at 25°C for 2 hours to ensure that the battery temperature was 25°C. After charging the battery at 0.33C at 25°C to the charge cut-off voltage, constant voltage charging was continued at the charge cut-off voltage until the current reached 0.05C and the charge was cut off (where C0 represents the rated capacity of the battery). After the battery was left at 25°C for 1 hour, it was discharged at 0.33C at 25°C to the discharge cut-off voltage, and the total discharge energy of the battery was recorded as E0;

[0184] Measure the battery volume as V0;

[0185] Battery volume energy density = battery discharge energy E0 / battery volume M0.

[0186] III. Analysis of test results of various embodiments and comparative examples

[0187] The batteries of the embodiments and comparative examples were prepared according to the above method, and various performance parameters were measured. The results are shown in Tables 1 to 4 below.

[0188] Table 1

[0189]

[0190] Table 2

[0191]

[0192] The positive electrode plates in Examples 1-21 all include a current collector and a positive electrode film layer located on at least one side of the current collector, the positive electrode film layer includes a first region and a second region, the particle size distribution index of the active material in the first region is smaller than the particle size distribution index of the active material in the second region, wherein the particle size distribution index refers to the ratio of the standard deviation of the active material particle size to the average particle size, the first region refers to the region where the positive electrode film layer extends vertically from the surface close to the current collector to the positive electrode film layer within a distance of h1, and the second region refers to the region where the positive electrode film layer extends vertically from the surface close to the current collector to the positive electrode film layer for a distance of h1 to H, wherein H is the thickness of the positive electrode film layer, and h1 is less than H. Figure 2-Figure 5It can be seen that the positive electrode film layer includes a first region and a second region. The particle size of the active material in the first region is more uniform, while the particle size deviation of the active material in the second region is large.

[0193] From the comparison between Examples 1-21 and Comparative Example 3, it can be seen that when the particle size distribution index of the active material in the first region is smaller than that of the active material in the second region and is 0.20-0.70, the flexibility of the pole piece can be improved, the ultimate compaction density that can be achieved by the pole piece can be improved, and the volume energy density of the battery can be increased.

[0194] Table 3

[0195]

[0196] From the comparison between Examples 1-21 and Comparative Example 2, it can be seen that the positive electrode sheet having the above characteristics can improve the flexibility of the electrode sheet and increase the ultimate compaction density that can be achieved by the electrode sheet compared to the positive electrode sheet with a single component.

[0197] From the comparison between Examples 1-3, 20-21 and Comparative Examples 2 and 3, it can be seen that when the particle size distribution index of the active material in the first region is 0.05-0.52, the flexibility and ultimate compaction density of the pole piece increase significantly. When the particle size distribution index of the active material in the first region is 0.1-0.5, the flexibility and ultimate compaction density of the pole piece are further significantly improved.

[0198] Table 4

[0199]

[0200] From the comparison between Examples 1-21 and Comparative Example 1, it can be seen that the positive electrode sheet having the above characteristics can increase the ultimate compaction density that can be achieved by the electrode sheet compared to the positive electrode sheet with a single component, and improve the volume energy density of the battery cell.

[0201] From the comparison between Examples 1-3, 20-21 and Comparative Examples 1 and 3, it can be seen that when the particle size distribution index of the active material in the first region is 0.05-0.52, the ultimate compaction density of the pole piece and the volume energy density of the battery increase significantly. When the particle size distribution index of the active material in the first region is 0.1-0.5, the ultimate compaction density of the pole piece and the volume energy density of the battery further increase significantly.

[0202] It can be seen from Examples 1 and 4-7 that when the average particle size of the active material in the first region is 150 nm-2000 nm, the battery has excellent flexibility, high ultimate compaction density and volume energy density.

[0203] From the comparison between Examples 5-7 and Example 4, it can be seen that when the average particle size of the active material in the first region is 300nm-2000nm, the flexibility, ultimate compaction density and volume energy density of the battery are improved simultaneously.

[0204] As can be seen from Examples 8-10, in the second region, when the percentage of active materials with a particle size of 50nm-200nm is 10% to 50% based on the total amount of active materials, the battery has excellent flexibility, high ultimate compaction density and volume energy density. In the second region, when the percentage of active materials with a particle size of 50nm-200nm is 10%-25% based on the total amount of active materials, the flexibility, ultimate compaction density and volume energy density of the battery are more significantly improved.

[0205] It can be seen from Examples 1 and 11-13 that in the second region, when the cross-sectional area percentage of the active material with a particle size of not less than 1500 nm is 5%-25% based on the total cross-sectional area of ​​the active material, the battery has excellent flexibility, high ultimate compaction density and volume energy density. In the second region, when the cross-sectional area percentage of the active material with a particle size of not less than 1500 nm is 10%-25% based on the total cross-sectional area of ​​the active material, the flexibility, ultimate compaction density and volume energy density of the battery are more significantly improved.

[0206] It can be seen from Examples 1 and 14-15 that the specific surface area of ​​the active material in the first region is low, so that the amount of binder in the first region can be reduced compared to the amount of binder in the second region, thereby improving the flexibility and ultimate compaction density of the electrode and increasing the volume energy density of the battery.

[0207] It can be seen from Examples 1, 16-19 that when the ratio of the thickness of the first region to the thickness of the positive electrode film layer is 1:10 to 5:10, the battery has excellent flexibility, high ultimate compaction density and volume energy density. When the ratio of the thickness h1 of the first region to the thickness H of the positive electrode film layer is 2:10-4:10, the flexibility, ultimate compaction density and volume energy density of the battery are more significantly improved.

[0208] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and the same effect as the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode sheet, characterized in that: It includes a current collector and a positive electrode film layer located on at least one side of the current collector, the positive electrode film layer includes a first region and a second region, the particle size distribution index of the active material in the first region is smaller than the particle size distribution index of the active material in the second region, wherein the particle size distribution index refers to the ratio of the standard deviation of the active material particle size to the average particle size, the first region refers to the region where the positive electrode film layer extends vertically from the surface close to the current collector to the positive electrode film layer within a distance of h1, and the second region refers to the region where the positive electrode film layer extends vertically from the surface close to the current collector to the positive electrode film layer for a distance of h1 to H, wherein H is the thickness of the positive electrode film layer, and h1 is less than H. Optionally, the difference between the particle size distribution index of the active material in the second region and the particle size distribution index of the active material in the first region is 0.08-0.80, and can be optionally 0.20-0.

70.

2. The positive electrode sheet according to claim 1, characterized in that: The particle size distribution index of the active material in the first region is 0.05 to 0.52, and can be optionally 0.1 to 0.

5.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The particle size distribution index of the active material in the second region is 0.60 to 0.82, and can be optionally 0.65 to 0.

78.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The average particle size of the active material in the first region is 150 nm-2000 nm, and can be optionally 300 nm-2000 nm.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: In the second region, based on the total amount of active materials, the percentage of active materials having a particle size of 50 nm to 200 nm is 10% to 50%, and may be 10% to 25%.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: In the second region, based on the total cross-sectional area of ​​the active material, the cross-sectional area percentage of the active material having a particle size of not less than 1500 nm is 5%-25%, and optionally 10%-25%.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The specific surface area of ​​the active material in the first region is 4-14 m 2 / g, optional 6-12m 2 / g.

8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The mass percentage of the binder in the first region is lower than the mass percentage of the binder in the second region. The mass percentage of the binder in the first region is the ratio of the mass of the binder in the first region to the mass of the positive electrode film layer in the first region, and the mass percentage of the binder in the second region is the ratio of the mass of the binder in the second region to the mass of the positive electrode film layer in the second region.

9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The mass percentage of the binder in the first region is 0.5%-2.5%, and can be optionally 1.5%-2%.

10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The ratio of h1 to H is 1:10 to 5:10, and can be optionally 2:10-4:

10.

11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: The surface density of the positive electrode film layer is 350 mg / 1540.25 cm 2 -500mg / 1540.25cm 2 .

12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: The active material in the first region and / or the second region includes a polyanionic compound.

13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: The positive electrode film layer is prepared by one-time coating using a double-sided double-cavity coating machine.

14. A secondary battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 13.

15. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 14.

Citation Information

Cited By

  • Positive electrode sheet, secondary battery, and electric device

    EP4648125A1

  • Battery cell, battery device, and electric device

    WO2026152935A1

  • Battery cell, manufacturing method therefor, battery apparatus and electrical apparatus

    WO2026157408A1

  • Lithium ion secondary battery, battery device, electric device, preparation method for positive electrode active material and preparation method for positive electrode sheet

    WO2026199526A1

  • Battery cell, battery apparatus and energy storage apparatus

    WO2026200072A1